Foreign language teaching (2024)
The present issue if yet another milestone in the years of collaboration between Universidad Pedagógica y Tecnologica de Colombia and Universidad Veracruzana. Our experience has shown us that the best way forward for the development of academic institutions and scholars is collaboration and cooperation in joint ventures, whether they are co-authored articles, organization and participation in conferences, teacher and student exchanges, or co-advising students working on their dissertations, to name a few instances. Instant communication through the Internet, computers and mobile devices, has made it easier to share papers, carry out projects, participate in research groups, and work together on papers written by people living in different countries.